Isolated ipsilateral shoulder and elbow dislocation - Milenković Bojan; Bilanović Miljan; Timotijević Slađan; Tatić Miroslav; Kolak Đorđe (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Joint dislocation is the loss of congruence of the joint surfaces. This is a relatively common injury of the musculoskeletal injury. Among the large joints, shoulder joint dislocation has the highest incidence of 24/100,000/year, of which 94–97% are anterior, 1% are inferior, and the remaining injuries are posterior shoulder dislocations. The second most frequent injury is elbow dislocation, with an incidence of 5.2/100,000/year. Among these, over 80% are posterolateral dislocations. Case outline. A 57-year-old female patient was injured during an accidental ground-level fall sustaining combined injuries – anterior dislocation of the shoulder joint and a posterolateral dislocation of the elbow joint. Upon sustaining the described injuries, she was treated conservatively with good functional results. Conclusion. A review of the literature reveals that the combination of ipsilateral shoulder and elbow joint dislocations is a rare injury, with shoulder dislocation often being overlooked. Proper anamnesis, along with a thorough examination of the joints both proximally and distally to the injured joint, is crucial. If performed adequately, these injuries can often be successfully managed nonoperatively, with closed reduction, immobilization, and rehabilitation, leading to satisfactory functional recovery.